2020
DOI: 10.1088/2043-6254/ab6cfd
|View full text |Cite
|
Sign up to set email alerts
|

Influence of size and surface acidity of silica nanoparticles on inhibition of the formation damage by bentonite-free water-based drilling fluids. Part II: dynamic filtration

Abstract: Although the application of nanoparticles in drilling fluid has been reported under static test by our research group, understanding inhibition formation of damage by filtration volume reduction in porous media under dynamic conditions is still a crucial issue. In this research, synthesised silica nanoparticles modified with acid treatment (Si11A) evaluated in previous results in the bentonite-free water-based drilling fluid (BFWBM) in static tests were analysed in the coreflooding test under dynamic and reser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 51 publications
(55 reference statements)
1
14
0
Order By: Relevance
“…NP content ≥0.3 wt % likely promoted NP aggregation, which, in turn, generated a thick filter cake, as reported in Table , allowing large filtrate volume through. This effect had been observed through experiments in previous studies that had been experimentally demonstrated by our research group . NP content up to 0.1 wt % reduced the filter cake thickness by ∼35% and permeability by ∼70%, relative to the base BFWBM.…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…NP content ≥0.3 wt % likely promoted NP aggregation, which, in turn, generated a thick filter cake, as reported in Table , allowing large filtrate volume through. This effect had been observed through experiments in previous studies that had been experimentally demonstrated by our research group . NP content up to 0.1 wt % reduced the filter cake thickness by ∼35% and permeability by ∼70%, relative to the base BFWBM.…”
Section: Resultssupporting
confidence: 79%
“…Subsequently, a low-permeability and porosity filter cake is observed . Moreover, lower filtrate volume through porous media under dynamic filtration has been reported in the presence of SiO 2 NPs . However, the exact mechanism through which the SiO 2 NPs help promoting the filtration properties of BFWBM was not investigated.…”
Section: Introductionmentioning
confidence: 99%
“…The oil and gas industry is aware of the potential of nanotechnology, with an increasing number of publications in specialized literature focused on experimental and simulation developments of nanomaterials and nanofluids for application in different areas. These relevant areas include drilling, completion, improved oil recovery (IOR), enhanced oil recovery (EOR), formation damage, , and wastewater treatment, , among others. Nevertheless, different challenges arise for the scaling up of the different developments.…”
Section: Introductionmentioning
confidence: 99%
“…However, the solvent needs to be compatible with the membrane . In particular, in the formulation process of polymeric nanoparticles, dialysis is a frequently applied technique. , Such particles can be labile against forced movements for, e.g., by applying pressure or vacuum for filtration. , Therefore, diffusion based dialysis is an ideal technique to gently purify nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…22,23 Such particles can be labile against forced movements for, e.g., by applying pressure or vacuum for filtration. 19,24 Therefore, diffusion based dialysis is an ideal technique to gently purify nanoparticles.…”
Section: ■ Introductionmentioning
confidence: 99%